Traduire la métaphore surréaliste - Tania Collani (Ksiegarnia Akademicka Publishing, 2017)
Translating Surrealist Metaphors. André Breton’s Nadja, the Marvelous and Its Translations into English and Italian Starting from Michael Riffaterre’ analysis of conceits (or long metaphors) within the Surrealist literary production (1969), this article aims to take into account the metaphorical code’s lexicon as well as the expressions forming the dense network of images which constitutes the Surrealist marvelous. The corpus is focused on André Breton’s Nadja (in its two French editions of 1928 and 1963), as well as on its English translation (by Richard Howard in 1960) and Italian translation (by Giordano Falzoni in 1972). After tracing in texts source a set of essential and sensitive words for the creation of the marvelous effect within the Surrealist production, we will see how the target texts take into account the rational analogies canvas woven by Breton.